AB0109 Autophagy inhibitor regulates apoptosis and proliferation of synovial fibroblasts through the inhibition of pi3k/akt pathway in collagen-induced arthritis rat model. (15th June 2017) - Li, S; Li, F; Chen, WJ; Deng, C
Abstract : Background: Mounting studies have illustrated an important role of autophagy in various diseases, but few studies have reported its contribution to rheumatoid arthritis (RA) and the underlying mechanism is largely unknown. Objectives: This study aimed to investigate whether autophagy inhibitors could regulate apoptosis and proliferation through PI3K/AKT pathway in RA. Methods: RA animal model was established by collagen induction. General observations and degree of joint swelling were observed. Inflammatory response, cell survival related factors and apoptosis were also detected in synovial fibroblasts. In addition, cultured rheumatoid arthritis fibroblast-like synoviocytes (RA-FLS) were subjected to TNF-α treatment in vitro, and TNF-α induced cell autophagy, synovial cell proliferation and apoptosis were detected. Moreover, cell cycle and cytokine secretion protein, along with the above parameters, were analyzed. Results: Results from the animal model showed that autophagy inhibitors could attenuate inflammatory reaction and synovial hyperplasia, while promoted synovial fibroblasts apoptosis. Meanwhile, inhibition of autophagy promoted cell apoptosis and reversed cell proliferation in vitro, also blocked cell in the G2/M arrest and reduced the S phase cells. Furthermore, inhibition of PI3K/AKT pathway reversed TNF-α mediated autophagy and cytokine secretion. Conclusions: autophagy inhibitors could mitigate inflammation response, inhibiting RA-FLS cell proliferation while promoting cell apoptosis by PI3K/AKT pathway. References: Neumann, E., et al., Rheumatoid arthritis progression mediated by activated synovial fibroblasts. Trends in Molecular Medicine, 2010. 16(10): p. 458–68. Feng, Y., et al., The Role of Autophagy in Rheumatic Disease. Current Drug Targets, 2016. Kenific, et al., Cellular and metabolic functions for autophagy in cancer cells. Trends in Cell Biology, 2015. 25(1): p. 37–45. Yan, H., et al., Suppression of experimental arthritis through AMP-activated protein kinase activation and autophagy modulation. Journal of Rheumatic Diseases & Treatment, 2011. 1(1). Qu, Y., et al., MicroRNA-126 affects rheumatoid arthritis synovial fibroblast proliferation and apoptosis by targeting PIK3R2 and regulating PI3K-AKT signal pathway. 2016. García, S., et al., Akt activity protects rheumatoid synovial fibroblasts from Fas-induced apoptosis by inhibition of Bid cleavage. Arthritis Research & Therapy, 2010. 12(1): p.: R33. Acknowledgements: This work was supported by grants from the National Natural Science Foundation of China Youth Foud (81302567) and Basic scientific research service fee of Central South University (2012QNZT138) to Dr. Shu Li. Disclosure of Interest: None declared